PERANCANGAN AKUISISI DATA SUMBER INFRA MERAH SEBAGAI AWAL PENELITIAN SISTEM SEEKER BERBASIS INFRA MERAH - Wahyudi, Agus Hendra; Prabowo, Gunawan S (BRIN Publishing, 2010)
Diagnostic tool in the thermal imaging using the thermovision has been developed to characterize the plume gas of solid AP-HTPB rocket propellant. The data Acquisition of the infrared source has been developed based on microcontroller and labview as a Software. This software can increase the capability of the thermovision camera with the real time process. Infrared source BaF2 was used as an object and this test has given the result: voltage 1.8 volt, thermal 390 Kelvin, and can be converted to 7-8 um wavelength. In the future, this system can be integrated with the actuator robotic or the fin of the rocket.